Using Mobile Instant Messaging in Teaching Vocabulary to Pre-intermediate EFL Learners: The Case of WhatsApp - Ehsan Namaziandost; Sajad Shafiee; Ray Suryadi (Journal of English Education, 2020)
Smartphones are becoming an increasingly common part of our daily lives. Applications used in these systems are extremely varied due to their extraordinary efficiency. With respect to language teaching, the use of these technologies has opened up new doors, changing innovatively the way teachers teach and students learn. Accordingly, this study aimed to find out the impacts of using WhatsApp as a mobile instant messaging application on teaching vocabulary among pre-intermediate EFL learners. To this end, 60 Iranian pre-intermediate EFL learners were selected from a private English Language Institute. Then, they were randomly assigned to two equal groups- an experimental group and a control group. They were pre-tested by a researcher-made vocabulary test.  Then, the treatment was applied to both groups. As the treatment, the control group was taught with traditional activities whereas the experimental group was taught with the use of mobile application (WhatsApp). At the end of the instruction, a researcher-made vocabulary post-test was administered. The results of independent samples t-test and one-way ANCOVA indicated that the experimental group had better performance on the post-test compared to control group revealing the usefulness of the mobile application utilized in this study on learning vocabulary.